Identification instrument of talent screening toward prospective art & design students / Syahrini Shawalludin...[et al.] - Shawalludin, Syahrini; Mohamed Salim, Neesa Ameera; Mamat Nawi, Azmir; Md Hashim, Azhari (Universiti Teknologi MARA, Kedah, 2020)
Candidate from SPM (Sijil Pelajaran Malaysia), who’s wishing to pursue in art and design studies will apply for courses under Faculty Art & Design. The Faculty of Art & Design, Universiti Teknologi MARA (UiTM) offers programs for Diploma, Undergraduate and Post Graduate and its has a total of nine programs are offered; Fine Arts, Graphic & Digital Media, Fashion, Industrial Design, Textile Design, Fine Metal, Ceramics, Fine Art and Printing Technology. Due to the interview, the selection process will be selected through a screening process inclusive of an interview session, drawing test, and the color-blind test that is compulsory for Diploma intake. The study argues how the current and past practice on screening traces and identifies the talent in art and design since the candidates have limited knowledge and exposure in the ten areas offered. The knowledge of the past practice is given by the lecturer or in charge person in simple explanation either in academic mission conducted by UiTM secretariat or during an interview session. Consequently, this also affects the interest, learning process, potential skills, and limits career development if the wrong programs are offered to them. This study identifies a solution in identifying the relevant talent and aptitude in art and design. A total of 148 candidates were involved in this study. An instrument in a form of the questionnaire was given to the candidates, which provide a systematic criterion in determining if the candidate has interest and talent in the nine areas provided. This study focuses on the importance of the talent identificationscreening instrument to assess talent for potential students who plan to embark their studies under the Faculty of Art & Design in Universiti Teknologi MARA (UiTM). The study suggests and defines the talent screening instrument is an added value to the talent identification process which has been justified relevant and beneficial to be implemented to the student selection process.